2014
DOI: 10.1111/echo.12666
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Speckle Tracking Echocardiography Prognostic Parameters in Patients after Acute Myocardial Infarction

Abstract: The assessment of LV function with STE may improve cardiovascular risk prediction in postmyocardial infarction patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
(48 reference statements)
0
17
0
1
Order By: Relevance
“…There were 11 studies assessing adverse remodeling [1424], 11 assessing reverse remodeling [2535] and 1 assessing both outcomes [36]. All patients reported in these studies had a successfully revascularized first STEMI (as defined by TIMI flow>2) except for 2 studies in which both STEMI and NTEMI patients were included [19,36]; only 2 studies included medical revascularization with thrombolysis. Most studies included a mixed STEMI population, with both anterior and inferior localizations; only 5 studies [15, 20, 26, 28, 32] included patients with anterior STEMI.…”
Section: Resultsmentioning
confidence: 99%
“…There were 11 studies assessing adverse remodeling [1424], 11 assessing reverse remodeling [2535] and 1 assessing both outcomes [36]. All patients reported in these studies had a successfully revascularized first STEMI (as defined by TIMI flow>2) except for 2 studies in which both STEMI and NTEMI patients were included [19,36]; only 2 studies included medical revascularization with thrombolysis. Most studies included a mixed STEMI population, with both anterior and inferior localizations; only 5 studies [15, 20, 26, 28, 32] included patients with anterior STEMI.…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent recoil of twist deformation is associated with the release of restoring forces, which contribute to LV diastolic relaxation and early diastolic filling. 17 Several studies have described the clinical relevance of LV twist, [8][9][10] which is predominantly governed by apical rotation. 22 Diastolic untwisting of the LV also plays an important role in diastolic suction.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The effects of CSF, and subsequent inadequate blood supply, on myocardial functions are not known. [8][9][10][11][12] STE enables a noninvasive examination of dynamic LV parameters, such as strain, twist/torsion, and rotation. [5][6][7] However, the effect of CSF on left ventricular twist functions has not been assessed.…”
mentioning
confidence: 99%
“…Several studies have determined that 2D speckle-tracking derived LV strain parameters provides valuable prediction of subsequent cardiac events and outcome in patients with AMI who have been treated by primary PCI [25,26]. However, data about the early prognostic value of LV strain parameter is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the long-term prognostic relevance of strain echocardiography after AMI [21][22][23][24][25][26][27][28][29]. However, the short-term prognostic value of strain echocardiography in patients with STEMI has not been well evaluated.…”
Section: Introductionmentioning
confidence: 99%